Electrochemical Bonding of Hydrogels at Rigid Surfaces. Issue 12 (16th November 2022) - Qiu, Xiaxin; Huang, Xiaowen; Zhang, Lidong
Abstract: Flexible hydrogels can be chemically/physically bonded on soft surfaces. However, there is a lack of a facile method to build strong interfacial adhesion between hydrogel and various rigid surfaces. Herein, an electrochemical bonding protocol, which improves the interfacial adhesion energy of hydrogel from initial 8 to 3480 J m −2, ≈435 times enhancement at rigid glass surface, superior to the most of traditional methods, is proposed. A series of electrochemical bonding models to analyze the bonding mechanism, is demonstrated. The results indicate that the electrode reactions generate Fe 3+ ions at the anode and OH − ions at the cathode, which migrate and react to form nanoparticles of Fe(OH)3 . These nanoparticles form hump‐like physical structures at the interface and work as mechanical‐bonding sites, enabling the strong interfacial adhesion. Upon applying acidic solution to decompose the nanoparticles, the strong adhesion can be weakened to easily remove hydrogel from the bonded surface. The electrochemically‐bonded hydrogel can maintain its adhesion in water, which enables the electrochemical bonding of hydrogels for repairing various damaged surfaces such as plastic water tubes/bags, indicating promising potential for adhesive engineering applications. Abstract : This work reports an electrochemical bonding protocol, which can improve interfacial adhesion of hydrogel from initial 8 to 3480 J m –2, ≈435 times enhancement at rigid glass surface. The strong adhesion is caused by electrochemistry‐produced nanoparticles of Fe(OH)3, which work as mechanical‐bonding sites to fix the hydrogel on glass surface.